ChemInform Abstract: Introducing a Large Polar Tetragonal Distortion into Ba‐Doped BiFeO3 by Low‐Temperature Fluorination. Issue 6 (February 2015) - Clemens, Oliver; Kruk, Robert; Patterson, Eric A.; Loho, Christoph; Reitz, Christian; Wright, Adrian J.; Knight, Kevin S.; Hahn, Horst; Slater, Peter R.
Abstract Bi1‐xBaxFeO3‐x/2 (x = 0.2, 0.3) phases are synthesized by solid state reaction of stoichiometric mixtures of BaCO3, Bi2O3, and Fe2O3 (850—920 °C, 30—45 h, yield given in g).